'Student voice in learning: instrumentalism and tokenism or opportunity for altering the status and positioning of students?'. (3rd April 2019) - Charteris, Jennifer; Smardon, Dianne
ABSTRACT: Student voice literature has been well mapped with a range of participatory frameworks and typologies over the last three decades. These acknowledge neoliberal uses of voice that reflect a pervasive marketised approach to education, where young people are consumers, teachers surveilled, and leaders are wedged between government and community accountability. We draw upon typologies from the field to investigate Principals' conceptions of student voice in Aotearoa/New Zealand schools. Practitioner awareness of the instrumentalism of particular voice strategies and associated critiques of their application provides alignment with a conception of education as a mode of making explicit social and political practice. The article highlights tensions where systemic improvement is prioritised over student agency and the right of young people to democratic participation in their schooling.